ANALISIS AKUNTANSI KANTOR PUSAT DAN KANTOR CABANG PADA UD. SINAR TERANG (Lembaga Pengembangan Kinerja Dosen, 2023)
Sinar Terang have operating for 5 years and the embracement have operating for 3 years. The main of this research is analysis accountancy in central and the embracement us UD. Pasifik Elektrik. This research be located on Jalan. Harapan Raya, Pekanbaru and on Jalan Pasir Putih, Kampar. This research need the central finance report in 2015 and the embracement finance report in 2015 plus journals which be recorded by company. Making joint financial statements, it is necessary need to record internal transactions and elimination journals between the central office and the embracement office. The recording of internal transactions consists of merchandise receiving journals from central office, and cash deposit journals fromembracement offices. Elimination journals consists of adjusting entries for SKHBC, earnings collection correction journal, central office elimination journal and the embracement office, and the embracement office elimination journal. The result of this research is the combined income statement which is Rp20.025.002 and the reports of combined financial position is Rp1.664.074.675.